Vertical axillary thoracotomy, anesthetic considerations included in the application of modifications - Rodolfo Eliseo Morales Valdés; Laylette Acosta Roca; Yohandys Duniel Pérez Días; Antonio Ismael Aparicio Morales; Yoandy López de la Cruz; Rodolfo Morales Mato (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Vertical axillary thoracotomy is a surgical procedure that allows multiple techniques to be performed for the diagnosis and treatment of chest diseases, an area that involves special anesthetic considerations. The present study aims to expose determinants for the anesthetic management of patients operated on for axillary thoracotomies. A bibliographic review was carried out by searching databases (Medline / Pubmed and Hinari), including the terms: vertical axillary thoracotomy, anesthetic management and thoracic surgery. The determinants identified within anesthetic management during vertical axillary thoracotomy were preoperative evaluation, monitoring, airway management, ventilation strategy, anesthetic treatment, and immediate postoperative analgesia. According to the needs and conditions of the team, it was determined to establish as a priority the defense of the optimal moment of muscle relaxation. Hemodynamic control of the patient, pulmonary isolation, muscle relaxation for the surgical approach, pulmonary ventilation, and perioperative analgesia continue to be the cornerstone of anesthetic management in vertical axillary thoracotomy today.